2009
DOI: 10.1175/2009mwr2679.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Humidity on Tropical Cyclone Size

Abstract: Observations demonstrate that the radius of maximum winds in tropical cyclones (TCs) can vary by an order of magnitude; similar size differences are evident in other spatial measures of the wind field as well as in cloud and precipitation fields. Many TC impacts are related to storm size, yet the physical mechanisms that determine TC size are not well understood and have received limited research attention. Presented here is a hypothesis suggesting that one factor controlling TC size is the environmental relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
199
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(246 citation statements)
references
References 51 publications
39
199
3
Order By: Relevance
“…Both studies detected a rather weak dependence of storm intensity with regard to environmental relative humidity in 3-D model simulations. Moreover, the sensitivity of TC size to RH ref in case I corresponds with results from the modelling study by Hill and Lackmann (2009), who found that the lateral extent of TCs increases with increasing environmental moisture content. As pointed out by Gray (1979), an enhanced relative humidity at mid-tropospheric levels is favourable to the formation of TCs and, hence, expected to be a determining factor with regard to their frequency of occurrence.…”
Section: Environmental Relative Humidity and Temperature Stratificationsupporting
confidence: 83%
See 1 more Smart Citation
“…Both studies detected a rather weak dependence of storm intensity with regard to environmental relative humidity in 3-D model simulations. Moreover, the sensitivity of TC size to RH ref in case I corresponds with results from the modelling study by Hill and Lackmann (2009), who found that the lateral extent of TCs increases with increasing environmental moisture content. As pointed out by Gray (1979), an enhanced relative humidity at mid-tropospheric levels is favourable to the formation of TCs and, hence, expected to be a determining factor with regard to their frequency of occurrence.…”
Section: Environmental Relative Humidity and Temperature Stratificationsupporting
confidence: 83%
“…It can also be seen that the sensitivity of the intensity to RH ref is stronger in case N than in case I. The latter result is closer to findings by Wang (2009) and Hill and Lackmann (2009). Both studies detected a rather weak dependence of storm intensity with regard to environmental relative humidity in 3-D model simulations.…”
Section: Environmental Relative Humidity and Temperature Stratificationsupporting
confidence: 82%
“…A comparison of precipitable water values when both TCs were located near this area (Figure 6c,d) shows that values for Irene exceeded 50 mm (Figure 6d) while those for Floyd approximated 40 mm. This finding supports previous research showing that higher amounts of moisture in the environment surrounding a TC can lead to a larger storm with more wide-spread rainfall [30][31][32][33][34]66].…”
Section: Rainfall Distribution Of Modern Stormssupporting
confidence: 91%
“…As a result, anything that influences the extent of a storm can also affect the track. In model simulations, this can include the initial TC size (e.g., Emanuel 1986;Rotunno and Emanuel 1987;Bender et al 1993;Leroux 2010;Xu and Wang 2010), environmental factors such as relative humidity (Hill and Lackmann 2009b;Wang 2009) and large-scale flow patterns (Liu and Chan 2002;Kimball 2006), and model physical parameterizations including cloud microphysics and cloud-radiative feedback (Fovell and Su 2007;Fovell et al , 2010. Asymmetries in convective heating, responding at least in part to the beta effect, can also significantly modulate motion (Wu and Wang 2000;Fovell et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In many applications, parameters c and d have been constrained to be equal (Chan and Williams 1987;DeMaria 1987;Fiorino and Elsberry 1989a;Hill and Lackmann 2009b) or d has been given a fixed value, such as unity (e.g., Smith 1993; Leslie and Holland 1995;Holland et al 2010;Qiu et al 2010). Other profiles also exist (e.g., Fujita 1952;Smith et al 1990;Emanuel 2004;Willoughby et al 2006), including a recently revised version of H80 (Holland et al 2010).…”
Section: Introductionmentioning
confidence: 99%